Study of the Efficiency of a Double-chambered Microbial Fuel Cell using Citrobacter sp - Sultana, Rabiya; Adhikary, Nirab. C.; Kalita, Mohan. C.; Talukdar, Narayan. C.; Khan, Mojibur. R. (International Journal of Scientific Research in Biological Sciences, 2019)
Microbial fuel cells (MFCs) are devices that use bacterial metabolism to convert chemical energy in organic matter to electrical energy from a wide range of organic substrates. In this work, the efficiency of a double-chambered microbial fuel cell was studied by taking Citrobacter sp.as the bacterium of interest, under different operational conditions with sucrose as the carbon source. Both the chambers of the MFC were separated by Nafion i.e. the proton exchange membrane (PEM) while the carbon cloths act as the respective electrodes. The maximum power density measured in this system was found as 125.67 mW/m². In this study, the growth condition of the bacteria was optimized for ambient temperature, which clearly revealed the temperature dependence of the MFC system for production of maximum current and voltage. Moreover, a pH optimization test of the MFC system was performed wherein the performance of the Citrobacter sp. was found to be better at pH 7.4 as compared to other pH values.